Searching for justice after the Holocaust : fulfilling the Terezin declaration and immovable property restitution - Bazyler, Michael J.; Boyd, Kathryn Lee; Nelson, Kristen (Lawyer); Shah, Rajika (New York, NY : Oxford University Press, 2019)
The Nazis & their cohorts stole mercilessly from the Jews of Europe. In the aftermath of the Holocaust, returning survivors had to navigate unclear & hostile legal paths to recover their stolen property from governments & neighbours who often had been complicit. While the return of Nazi-looted art & recent legal settlements involving dormant Swiss bank accounts, unpaid insurance policies & use of slave labour by German companies have been well-publicized, efforts by Holocaust survivors & heirs over the last 70 years to recover stolen land & buildings were forgotten. In 2009, 47 countries convened in Prague to deal with the lingering problem of restitution of prewar private, communal, & heirless property stolen during the Holocaust. The outcome was the Terezin Declaration on Holocaust Era Assets & Related Issues, aiming to 'rectify the consequences' of the wrongful Nazi-era immovable property seizures.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 9, 2019).
Keywords: Terezin Declaration on Holocaust Era Assets and Related Issues -- (2009 June 30); World War, 1939-1945 -- Claims; Jewish property; Holocaust, Jewish (1939-1945) -- Economic aspects; Warfare and Defence; European history